2017
DOI: 10.6106/jcepm.2017.3.30.030
|View full text |Cite
|
Sign up to set email alerts
|

Practical Approach for Pavement Treatment Decisions for Local Agencies

Abstract: Most local agencies such as counties and small cities continuously express difficulties in making technically and financially defensible decisions on their pavement infrastructure maintenance and rehabilitation. Unlike pavement systems managed by state highway agencies, the total lane-miles of many local pavements are significantly short and they are managed by a limited number of staff who typically have multiple responsibilities. Most local agencies also do not have historical pavement performance data and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…In another study, it was found that traffic volume, maintenance history and structural data are important factors in building PMS among Colorado local agencies (Hafez et al, 2019). In Iowa State, US, collection of pavement distress data is lacking in 70% (of 74 respondents) of the local agencies, and therefore subjective maintenance practice prevails (Abdelaty et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, it was found that traffic volume, maintenance history and structural data are important factors in building PMS among Colorado local agencies (Hafez et al, 2019). In Iowa State, US, collection of pavement distress data is lacking in 70% (of 74 respondents) of the local agencies, and therefore subjective maintenance practice prevails (Abdelaty et al, 2017).…”
Section: Introductionmentioning
confidence: 99%